Addressing recent criticisms against international arbitrations - Born, Gary (2016)
The last 30 years have been a really exceptional time for international arbitration. The author resembles international arbitration with the SevenKingdoms of “Game of Thrones” where everything went right under the umbrella of the New York Convention.Gary Born states: “Winter is Coming” for international arbitration. The arbitration community should be prepared to defend itself from a metaphorical “armyof undead” who could demand more government control of the arbitration process in the future. In that regard, the author states that instead of beinghunted in defending arbitration, we ought to hunt a little bit. The time to stop fending off attacks and start going on the offensive against arbitration’s critics have come.